KDM3A Inhibition Ameliorates Hyperglycemia-Mediated Myocardial Injury by Epigenetic Modulation of Nuclear Factor Kappa-B/P65 - Zhang, Bofang; Zhang, Jing; Liu, Gen; Guo, Xin; Liu, Xiaopei; Chen, Jing (Frontiers in Cardiovascular Medicine, 2022)
Objectives Even after the glucose level returns to normal, hyperglycemia-induced cardiac dysfunction as well as reactive oxygen species (ROS) generation, inflammatory responses, and apoptosis continued deterioration, showing a long-lasting adverse effect on cardiac function and structure. We aimed to unveil the molecular and cellular mechanisms underlying hyperglycemia-induced persistent myocardial injury and cardiac dysfunction. Methods and Results Recently, the accumulated evidence indicated epigenetic regulation act as a determining factor in hyperglycemia-induced continuous cardiovascular dysfunction. As an important histone demethylase, the expression of lysine-specific demethylase 3A (KDM3A) was continually increased, accompanied by a sustained decline of H3K9me2 levels in diabetic myocardium even if received hypoglycemic therapy. Besides, by utilizing gain- and loss-of-functional approaches, we identified KDM3A as a novel regulator that accelerates hyperglycemia-mediated myocardial injury by promoting ROS generation, aggregating inflammatory reaction, and facilitating cell apoptosis in vitro and in vivo. The KDM3A inhibition could significantly ameliorate the adverse effect of hyperglycemia in both diabetes model and diabetic intensive glycemic control model. Mechanically, our data uncovered that KDM3A could promote the expression and transcriptional activity of nuclear factor kappa-B (NF-κB/P65), and the succedent rescue experiments further verified that KDM3A regulates hyperglycemia-induced myocardial injury in an NF-κB/P65 dependent manner. Conclusion This study revealed histone-modifying enzymes KDM3A drives persistent oxidative stress, inflammation, apoptosis, and subsequent myocardial injury in the diabetic heart by regulating the transcription of NF-κB/P65.